KOMBINASI PENJUALAN KAIN BATIK MENGGUNAKAN METODE APRIORI - Yustina Retno Wahyu Utami; Hendro Wijayanto; Richi Adi Prasetyo (STMIK Sinar Nusantara, 2022)
The existence of operational activities selling batik cloth every day will increase more and more, If left alone, the transaction data will only become meaningless garbage. is an individual company that manufactures and sells batik with various types of batik. The types of batik include Batik Insights, Color Insights, Cash Written Batik, Fine Written Batik, Fine Granite Written Batik, Night Print Batik, Stamped Batik, Combined Batik, Dagel Batik. In processing sales data, it is still done manually, which only uses records and receipts, so the data only functions as an archive. The data used in this study are sales transaction data for 2 years with a total of 215 transactions. The purpose of this study is to implement apriori algorithm system for the combination of batik fabric sales on Dewi Ratih batik so that it can help to find out the types of batik that are most often purchased. The results of this study are to determine which combination of batik fabric sales are most often bought simultaneously by determining a minimum support of 30% and a minimum confidence of 70% with a comparison of Weka and PHP MysQL applications with an accuracy rate of 100%